Нова конструктивна форма жорсткого з’єднання монолітного залізобетонного перекриття з трубобетонною колоною - Кущенко, В. М.; Галущак, Ю. Г.; Kushchenko, V.; Halushchak, Y. (Видавництво Львівської політехніки, 2018)
Запропоновано нову конструктивну форму жорсткого з’єднання трубобетонної колони з монолітним залізобетонним перекриттям, яке створюється за рахунок використання сталевого елемента жорсткості, що складається з вертикальних сталевих пластин, що перетинають бетонне ядро колони і з’єднані з сталевою трубою зварними швами. Для забезпечення жорсткого з’єднання з трубобетонною колоною, конструкція перекриття містить сталеве полосове зовнішнє армування. Порівняльне чисельне моделювання напружено-деформованого стану конструкцій залізобетонного монолітного перекриття з різними умовами з’єднання з трубобетоною колоною, та наявністю зовнішнього сталевого полосового армування, показало ефективність запропонованого конструктивного рішення.

Basing on existent concrete filled tube to reinforced concrete ceiling joining constructive form research and investigation in reinforced concrete area analyzing, the new constructive form of rigid connection of concrete filled tube to sitecast reinforced concrete ceiling, which is enhanced by using steel rigid element which consists of vertical steel plates, which cross column concrete core, and welded to steel tube was offered. For providing the rigid connection with concrete filled tube column, construction of ceiling includes the stripes of external steel plate reinforcing, welded to steel rigid element and to concrete filled tube column’s steel casing. The comparative finite element modeling (FEM) analysis of tension-strain conditions of sitecast reinforced concrete ceiling construction with 477mm diameter concrete filled tube columns with soft and rigid conditions of joining of ceiling and column and using the stripes of external steel plate reinforcement in case of rigid connection was made using the Robot Structural Analysis. The first model included the regular sitecast reinforced concrete ceiling. The second model included the reinforced concrete ceiling with external steel plate reinforcement, modeled by equivalent rigidness finite elements. The comparative FEM proved the effectiveness of offered constructive decision by decreasing the bending moments in plate middle area on 42 %
New constructive form of rigid connection of sitecast reinforced concrete ceiling to concrete filled tube column
Keywords: монолітні конструкції; залізобетонне перекриття; зовнішнє полосове армування; трубобетонні конструкції; sitecast constructions; reinforced concrete ceiling; external plate steel reinforcing; concrete filled tube constructions; 624.012.45